No intrauterine vertical transmission in pregnancy with COVID-19: A case report. Issue 12 (December 2020) - Lv, Yantian; Gu, Binbin; Chen, Ying; Hu, Siming; Ruan, Ting; Xu, Guopeng; Ding, Jian; Xu, Xiao; Shen, Xinghua
Abstract: The coronavirus disease 2019 (COVID-19) has been a worldwide pandemic diseases, nearly 400, 000 people died at now. The data of status of pregnant women and neonates after infection of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is limited. We report a case of pregnant woman in her third trimester with critical COVID-19, and amniotic fluid, umbilical cord blood, placenta, and neonatal gastric fluid were retained during cesarean section. The SARS-COV-2 nucleic acid test results of these specimens were negative. There is no evidence of intrauterine vertical transmission during delivery in the third trimester, but the data are limited and need to be further explored.